A systematic comparison of intercultural and indigenous cultural dance education from a global perspective (2010–2024) - Liu, Weishan; Xue, Hanbing; Wang, Zi Yi (Frontiers in Psychology, 2024)
Cultural dance fosters social cohesion, emotional well-being, creative thinking, and cultural identity by conveying cultural values and social meanings. However, systematic comparative research on cross-cultural and indigenous cultural dance education remains limited. This study, adopting a global perspective, examines the current applications, core issues, and educational strategies in this field. Through a systematic literature review and grounded theory approach, the research scrutinizes studies conducted from 2010 to 2024. The results show that intercultural research primarily focuses on multicultural exchange, cultural integration of immigrant groups, and cultural acceptance among socioeconomically disadvantaged populations, highlighting the influence of intercultural adaptability and globalization. In contrast, indigenous cultural research emphasizes local culture and educational systems, with a particular focus on local cultural identity and educational reform. While both types of research reach a consensus on the importance of cultural transmission, diversity in teaching strategies, and the critical role of educators, significant differences remain in cultural identity and the design of educational content. Future research could concentrate on virtual dance education, innovation in indigenous cultures, the exploration of dance education’s role in mental health, and the deep integration of artificial intelligence into dance pedagogy. Furthermore, consideration of the potential impact of globalization and technological advancement on cultural identity and educational models will foster theoretical innovation and practical development in dance education.